OECS Education Reform Strategy: Summary, strategies and recommendations - Miller, Errol L. (1992)
This paper places the Consultation on Education Reform of the Organisation of Eastern Caribbean States (OECS), held in Antigua in July 1991, in context, and also reports on the end product: the Education Reform Strategy that was developed and approved by the OECS
Keywords: Organisation of Eastern Caribbean States